Formation of Ho-III Trinuclear Clusters and Gd-III Monodimensional Polymers Induced by ortho and para Regioisomers of Pyridyl-Functionalised beta-Diketones: Synthesis, Structure, and Magnetic Properties - Andrews, P.; Deacon, G.; Frank, R.; Fraser, B.; Junk, P.; Maclellan, J.; Massi, Massimiliano; Moubaraki, B.; Murray, K.; Silberstein, Morry (Wiley-VCH Verlag GmbH & Co, 2009)
Reaction of GdCl3(H2O)(6) and 1,3-bis(pyridin-4-yl)propane-1,3-dione in methanol with an excess of triethylamine produced a monodimensional polymeric chain [Gd(p-dppd)(3)-(H2O)](infinity), whereas treatment of HoCl3(H2O)(6) with 1,3-bis(pyridin-2-yl)propane-1,3-dione yielded a trinuclear cluster [Ho-3(o-dppd)(3)(mu(3)-OH)(2)(H2O)(4)Cl-2]Cl-2. The compounds were characterised by elemental analysis, IR spectroscopy and magnetism, and their structures were investigated by X-ray crystallography. The 8.20-mu(B) magnetic-moment value of the polymeric [Gd(p-dppd)(3)(H2O)](infinity), between 300 and 20 K, and the magnetisation isotherms (2-20 K; fields 0-5 T), are in agreement with essentially uncoupled single-ion Gd3+ f(7) centres, a small decrease in mu(eff) below 20 K being indicative of zero-field splitting. A temperature-dependent dc-susceptibility and magnetisation investigation of the trinuclear (tri-angular) [Ho-3(o-dppd)(3)(mu(3)-OH)(2)(H2O)(4)Cl-2]Cl-2 revealed that spin-orbit and ligand-field effects on the Ho3+ centres, leading to thermal depopulation of Zeeman levels and consequent decreases in mu(eff) values with decreasing temperature, are occurring rather than weak intra-cluster antiferromagnetic coupling. Frequency- and temperature-dependent ac-susceptibility studies on this homometallic Ho3+ cluster did not show clear evidence for slow magnetisation reversal, characteristic of single-molecule magnetism (SMM), and this contrasts with such behaviour recently reported, elsewhere, for a Dy3+ triangle having the same core structure but with different chelating {O,O} ligands.